2015
DOI: 10.1007/s00198-014-3004-y
|View full text |Cite
|
Sign up to set email alerts
|

The social gradient of fractures at any skeletal site in men and women: data from the Geelong Osteoporosis Study Fracture Grid

Abstract: Disadvantaged men and women have an increased fracture incidence compared to their less disadvantaged counterparts. The large differences in fracture rates between SES groups warrant further research into designing appropriate, targeted interventions for those demographics at most risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 28 publications
2
14
1
4
Order By: Relevance
“…The public health importance of the social gradient of osteoporosis is underscored by increased attention in recent years [27][28][29][30]. Yet, the underlying mechanism for that gradient remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The public health importance of the social gradient of osteoporosis is underscored by increased attention in recent years [27][28][29][30]. Yet, the underlying mechanism for that gradient remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The epigenetic signature is influenced by a multitude of environmental factors across the lifespan, and the epigenome appears to function as a vital conduit that transduces exposures into phenotypic expression and disease risk [15,31]. We suggest that understanding this mechanism with respect to specific social determinants may identify various entry points for interventions in order to reduce the prevalence of osteoporosis and, consequently, reduce the social gradient of osteoporotic fracture [27]. This paper proposes a conceptual model, based on the challenge posed by social disadvantage to achieving allostasis (the maintenance of stability, or homeostasis, through change [24]), and the 'threehit theory' of the allostatic load model as identified by McEwen et al [32], and later expanded upon by Daskalakis et al [33], whereby genetic predisposition provides the first 'hit' to allostasis, the early life environment provides the second, and later life environment provides the third.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle and risk-taking behaviours known to be associated with increased fracture risk are, in the majority, highly socially patterned (Brennan et al, 2014); these include smoking (Hiscock et al, 2012) and alcohol consumption (Mulia et al, 2008). However, even the prevalence of chronic diseases associated with fracture risk vary according to socioeconomic status, for instance diabetes (Krishnan et al, 2010, Agardh et al, 2007) and fracture history (Brennan et al, 2015). Our review showed substance abuse to be associated with a higher risk of fracture in indigenous populations (Leslie et al, 2006), as were lower income and area of geographic residence (Leslie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for fracture included as confounders in this study are age and sex (16, 17), and prevalence of fracture may be greater among people of lower socioeconomic status (30). For ALS, risk factors include age and sex (1).…”
Section: Methodsmentioning
confidence: 99%